2005
DOI: 10.1242/dev.01554
|View full text |Cite
|
Sign up to set email alerts
|

Retinoic acid signaling acts via Hox1 to establish the posterior limit of the pharynx in the chordate amphioxus

Abstract: expression of these endodermal genes in embryos treated with RA or the RA antagonist BMS009 indicates that Pax1/9, Pitx and Notch are probably more upstream than Otx and Nodal in the hierarchy of genes repressed by RA signaling. This work highlights the potential of amphioxus, a genomically simple, vertebrate-like invertebrate chordate, as a paradigm for understanding gene hierarchies similar to the more complex ones of vertebrates.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
99
0
3

Year Published

2008
2008
2018
2018

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 101 publications
(114 citation statements)
references
References 89 publications
(87 reference statements)
12
99
0
3
Order By: Relevance
“…Of interest, in later developmental stages, Pax2/5/8 expression diminishes in the most anterior part of the amphioxus endostyle at the time and location predicted from our observations in Oikopleura, corresponding to the stage at which Pax2/5/8 expression becomes restricted to the central part of the endostyle (Kozmik et al, 1999). Although Otx and Hox1 expression have not yet been investigated in the differentiated endostyle of amphioxus, Otx and Hox1 are expressed early in the pharyngeal endoderm from which the endostyle differentiates (Williams and Holland, 1996;Schubert et al, 2005). In the pharynx of 30-hpf amphioxus embryos, Otx is expressed anteriorly, and Hox1 is expressed posteriorly (Schubert et al, 2005), following the same order that we observed in the expression of the orthologs in Oikopleura when endostyle precursors differentiate from the pharyngeal primordium.…”
Section: Is the Ordered Expression Ofsupporting
confidence: 73%
See 2 more Smart Citations
“…Of interest, in later developmental stages, Pax2/5/8 expression diminishes in the most anterior part of the amphioxus endostyle at the time and location predicted from our observations in Oikopleura, corresponding to the stage at which Pax2/5/8 expression becomes restricted to the central part of the endostyle (Kozmik et al, 1999). Although Otx and Hox1 expression have not yet been investigated in the differentiated endostyle of amphioxus, Otx and Hox1 are expressed early in the pharyngeal endoderm from which the endostyle differentiates (Williams and Holland, 1996;Schubert et al, 2005). In the pharynx of 30-hpf amphioxus embryos, Otx is expressed anteriorly, and Hox1 is expressed posteriorly (Schubert et al, 2005), following the same order that we observed in the expression of the orthologs in Oikopleura when endostyle precursors differentiate from the pharyngeal primordium.…”
Section: Is the Ordered Expression Ofsupporting
confidence: 73%
“…Although Otx and Hox1 expression have not yet been investigated in the differentiated endostyle of amphioxus, Otx and Hox1 are expressed early in the pharyngeal endoderm from which the endostyle differentiates (Williams and Holland, 1996;Schubert et al, 2005). In the pharynx of 30-hpf amphioxus embryos, Otx is expressed anteriorly, and Hox1 is expressed posteriorly (Schubert et al, 2005), following the same order that we observed in the expression of the orthologs in Oikopleura when endostyle precursors differentiate from the pharyngeal primordium. It is thus possible that the genetic mechanisms that pattern the AP axis of the pharyngeal endoderm from which the endostyle derives also pattern the endostyle.…”
Section: Is the Ordered Expression Ofsupporting
confidence: 73%
See 1 more Smart Citation
“…In invertebrate chordates, as in other invertebrate deuterostomes, the establishment of left/right asymmetry probably involves the same gene hierarchy as in vertebrates (Chea et al, 2005;Duboc et al, 2004Duboc et al, , 2005. For example, as in vertebrates, homologs of shh, pitx, and nodal are all expressed asymmetrically during amphioxus development (Schubert et al, 2005;Yu et al, 2007). However, both in amphioxus (Schubert et al, 2005) and ascidians (Hinman and Degnan, 1998), treatments with exogenous RA do not obviously alter the establishment of the left/right body axis suggesting that a role for RA signaling in establishing global left/ right asymmetry in the embryo is a vertebrate innovation (Schubert et al, 2005).…”
Section: Mesoderm Somitogenesis and Left/right Asymmetrymentioning
confidence: 99%
“…In the cephalochordate amphioxus, which lacks migrating NCCs, patterning of the pharyngeal endoderm is also RA-dependent (Escrivà et al, 2002;Holland and Holland, 1996;Schubert et al, 2005). Treatments with exogenous RA lead to a loss of pharyngeal structures (e.g.…”
Section: Endoderm Patterning and Pharyngeal Developmentmentioning
confidence: 99%